Impact of molecular interactions with phenolic compounds on food polysaccharides functionality - Dobson, Corrine C.; Mottawea, Walid; Rodrigue, Alexane; Buzati Pereira, Bruna L. [UNESP]; Hammami, Riadh; Power, Krista A.; Bordenave, Nicolas (Elsevier, 2019)
Commercial trends based of the emergence of plant-based functional foods lead to investigate the structure-function relationship of their main bioactive constituents and their interactions in the food matrix and throughout the gastro-intestinal tract. Among these bioactive constituents, dietary polysaccharides and polyphenols have shown to interact at the molecular level and these interactions may have consequences on the polysaccharides physical and nutritional properties. The methods of investigation and mechanisms of interactions between polysaccharides and polyphenols are reviewed in light of their respective technological and nutritional functionalities. Finally, the potential impact of the co-occurrence or co-ingestion of polyphenols and polysaccharides on the technological and nutritional functionality of the polysaccharides are investigated.
Keywords: Dietary fibers; Flavonoids; Gut health; Nutritional functionality; Phenolic acids; Polyphenols; Polysaccharides; Structure function-relationship